2018
DOI: 10.1016/j.eatbeh.2018.02.006
|View full text |Cite
|
Sign up to set email alerts
|

BMI and disordered eating in urban, African American, adolescent girls: The mediating role of body dissatisfaction

Abstract: Body dissatisfaction explains some associations between excess body weight and subsequent disordered eating symptoms among early adolescent, African American girls. Body dissatisfaction, identified by screening, may be an indicator of further negative consequences, including disordered eating behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The home food environments of young individuals from low-SES households have been found to provide less access to healthy foods and to be characterised by more parental control over feeding when compared with the environments of young individuals with more household resources (127)(128)(129) . In addition to these challenges, there is evidence that weight-related concerns and disordered eating are prevalent among paediatric populations in low-income communities (132,152,(156)(157)(158) . The extent to which food insecurity and parental control over feeding may contribute to the development of disordered eating patterns among lowerincome households is an area of ongoing research.…”
Section: Discussionmentioning
confidence: 99%
“…The home food environments of young individuals from low-SES households have been found to provide less access to healthy foods and to be characterised by more parental control over feeding when compared with the environments of young individuals with more household resources (127)(128)(129) . In addition to these challenges, there is evidence that weight-related concerns and disordered eating are prevalent among paediatric populations in low-income communities (132,152,(156)(157)(158) . The extent to which food insecurity and parental control over feeding may contribute to the development of disordered eating patterns among lowerincome households is an area of ongoing research.…”
Section: Discussionmentioning
confidence: 99%
“…Fu et al 6 found that the body dissatisfaction rate among Chinese children and adolescents was 77.1%. Furthermore, Buckingham-Howes et al 7 reported that 60.4% of African American adolescent girls expressed body dissatisfaction and desired to be smaller. A study from Mulasi-Pokhriyal et al 8 indicated that 79% of girls and 69% of boys in the United States were dissatisfied with their body.…”
Section: Introductionmentioning
confidence: 99%
“…We are unaware of any studies that have examined yoga in relation to muscle enhancing behaviors in any population‐based studies. Young people from socially marginalized ethnic/racial and low socio‐economic backgrounds have been found to be at high risk for problematic eating and weight‐related outcomes (Neumark‐Sztainer, Wall, Larson, et al, 2012; Eisenberg, Wall, & Neumark‐Sztainer, 2012; Tester et al, 2016; West et al, 2019; Buckingham‐Howes et al, 2018; Najjar et al, 2018), but may be underserved with regard to prevention and treatment interventions (Waldron, Hong, Moskowitz, & Burnett‐Zeigler, 2018; Polo et al, 2019). It is crucial to learn more about how to help in promoting a healthy body image and prevent and reduce unhealthy muscle‐enhancing and disordered eating behaviors among diverse and potentially underserved populations.…”
Section: Discussionmentioning
confidence: 99%
“…While behaviors such as engaging in physical activity, eating varied nutrient-dense foods, and mindful eating are to be encouraged, other actions such as unhealthy weight control behaviors (e.g., skipping meals, taking diet pills, and self-induced vomiting) and use of muscle enhancers, such as steroids, are problematic (5,6). Research suggests that the prevalence of disordered eating and muscleenhancing behaviors may be equally high, or even higher, among adolescents from lower socio-economic and ethnic/racial minority backgrounds than among adolescents from white and middle or upper socio-economic backgrounds (2,(7)(8)(9)(10)(11). There is a need for more research on the prevalence, correlates, and use of potentially helpful strategies aimed at promoting a healthy body image and preventing the use of unhealthy behaviors aimed at changing body shape or size among populations that are likely to have been understudied and underserved in terms of prevention and treatment interventions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation